Homosexuality in the DSM: A Critique of Depathologisation and Heteronormativity - Hectors, Arin (New Zealand Sociology, 2023)
This article provides a critical overview of both the historical and current diagnostic categories from the Diagnostic and statistical manual of mental disorders (DSM) that perpetuate heteronormativity. By drawing on critical scholars from queer theory, transfeminism and Marxist fields, I analyse two diagnostic categories (gender identity disorder of childhood and transvestic disorder) to argue that, contrary to the official narrative presented by the American Psychiatric Association, such classifications pathologise queer sexualities and gender nonconformity. The article concludes by suggesting that the American Psychiatric Association should be held to account for the historical and contemporary harm caused by the pathologisation of homosexuality and gender nonconformity, and calls for an end to psychiatric research that furthers the development of such diagnostic categories.